The History of reading a reader - Towheed, Shafquat 1973-; Crone, Rosalind; Halsey, Katie (Routledge, 2011)
Summarises the main debates and perspectives shaping the field of reading. This title introduces key theorists such as Iser, Fish and Bakhtin. It surveys influential works and outlines important studies on mass reading. It focuses on specific communities such as Welsh miners, African American library users and Australian convicts.